2012
DOI: 10.1111/j.1467-9299.2011.02003.x
|View full text |Cite
|
Sign up to set email alerts
|

Symposium Overview: Conceptualizing New Governance Arrangements

Abstract: This symposium, ‘Conceptualizing New Governance Arrangements', takes up the challenge of refining governance theory to better integrate work in several disciplines, most notably politics, public administration and law. To this end, we argue for a theoretical framework that profiles three key dimensions of governance: institutional, political and regulatory. This framework, in our view, offers new insights into the nature and operation of various governance arrangements, and offers the potential to assess and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…Metagovernance, a concept first employed to analyze national‐level governance (Jessop ; Pierre and Peters ; Rhodes ), has recently been reconceptualized to consider governance occurring at the global level (see Derkx ; Derkx and Glasbergen ; Fransen ; Glasbergen ; Meuleman ). Referencing “the governance of governance,” metagovernance aims to explain and analyze efforts to oversee, manage, and coordinate complex, often fragmented, “lower level” governance arrangements such as networks, quasi‐markets, partnerships, self‐regulation, and private commercial and nonprofit entities (Bell and Hindmoor ; Bevir ; Jessop ; Pierre and Peters ; Rhodes ; Sørensen ; Tollefson, Zito, and Gale ; Torfing et al ).…”
Section: Comparison Of Metagovernance Functions For Fair Trade and Fsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metagovernance, a concept first employed to analyze national‐level governance (Jessop ; Pierre and Peters ; Rhodes ), has recently been reconceptualized to consider governance occurring at the global level (see Derkx ; Derkx and Glasbergen ; Fransen ; Glasbergen ; Meuleman ). Referencing “the governance of governance,” metagovernance aims to explain and analyze efforts to oversee, manage, and coordinate complex, often fragmented, “lower level” governance arrangements such as networks, quasi‐markets, partnerships, self‐regulation, and private commercial and nonprofit entities (Bell and Hindmoor ; Bevir ; Jessop ; Pierre and Peters ; Rhodes ; Sørensen ; Tollefson, Zito, and Gale ; Torfing et al ).…”
Section: Comparison Of Metagovernance Functions For Fair Trade and Fsmentioning
confidence: 99%
“…The FSC scheme emerged in the 1990s in a context of increased evidence of tropical deforestation and the limited effectiveness of international initiatives such as the International Tropical Timber Organization and the Tropical Timber Action Plan to halt it (Gale 1998;Humphreys 1996). In late 1990, the Rainforest Alliance announced its SmartWood certification program, which had just certified the Indonesian state-owned forest Perum Perhutani as "well-managed tropical woods" (Synnott 2005). With other organizations like Sustainable Certification Systems and the Sustainable Forestry Institute declaring intentions to develop their own proprietary schemes, concern grew over a potential for a "race to the bottom" in standards.…”
Section: Global Private Governancementioning
confidence: 99%
“…Despite the long-standing prominence of this approach to implementing law, NEG has recently arisen as a potential challenge to the status quo. Often characterized as emerging in response to the limits and/or failures of traditional approaches, NEG is seen by many to represent an alternative to traditional command and control approaches to making, implementing, and enforcing policy/regulation (Doelle et al 2012;Tollefson, Zito, and Gale 2012;Holley and Gunningham 2011;Bingham 2010;Trubek and Trubek 2007). Debates have accordingly arisen regarding the interaction and relation of NEG's form of governance and traditional hard law (Alexander 2009;Trubek and Trubek 2007).…”
Section: Literature On Neg and The Lawmentioning
confidence: 99%
“…Broadly, similar shifts toward collaborative and polycentric styles of governance have been thought about under alternative and distinct theories (Burris, Kempa, and Shearing ; Rhodes ; for disambiguation between theories, see Karkkainen ; Parker and Braithwaite ). However, in contrast to the wider new governance literature (e.g., Velluti ; Tollefson, Zito, and Gale ; de Búrca and Scott 2006), very few of these theories have focused on environmental and water policy making, which is the subject of this article (Sabel and Simon ).…”
Section: Introductionmentioning
confidence: 96%
“…"Government" in this sense can be regarded as sharing a family resemblance with the term "governance," because neither presupposes that government is limited to the exercise of power by the state. However, most "governance" research is oriented towards its political, institutional, and regulatory dimensions ( Jordan et al 2005;Tollefson et al 2012), whereas our focus is on the rationalities that underpin it, as revealed through practice.…”
Section: Governmentality and Technologymentioning
confidence: 99%